Determinants Of Intention To Use Islamic Mobile Banking On Millennial Generation: Evidence From Indonesia - Harahap, Darwis (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This review means to test and dissect the determinants of goals of utilizing Islamic mobile banking. The Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) was used to conduct the study. This theory uses performance expectations, effort expectations, social influences, facilitating conditions, price values, hedonic motivation, and habits as predictors of intentions to use Islamic mobile banking. The Islamic way of life is the new coding construct that this study adds to the UTAUT2 model. 155 respondents from Indonesia's millennial generation served as the sample for this study. With the Structural Equation Model (SEM) as the analysis model and Warp PLS version 7.0 as the software, this study employed a quantitative approach. This study shows that the intention to use Islamic mobile banking is positively and significantly influenced by hedonistic motivation, price value, and habits. In the meantime, intention to use Islamic mobile banking is positively and insignificantly affected by performance expectations of effort, social influences, and conditions. The decision to use Islamic mobile banking as part of an Islamic lifestyle is then influenced by the variables of social impact and insignificant habits. In the context of the intention to use the behavior of using Islamic mobile banking, the findings of this study are anticipated to contribute to the prediction of a more in-depth model of consumer behavior from an Islamic perspective.